DEVELOPING THE HUMAN RESOURCES EFFECTIVENESS THRUOGH TRAINING AND DEVELOPMENT - Okolie, Ugo Chuks (Annals of Spiru Haret University. Economic Series, 2020)
The environment of business is increasingly becoming more volatile and unpredictable and this randomness and disorder is draining potency form the over a century old bureaucratic paradigm that has dominated management practices across the globe. The fast pace of change is driving, obsolescence into yesterday’s breakthroughs and today’s success techniques cannot be extrapolated to solving tomorrow’s problems with guarantee. Organizations must find a way of embracing the 21st century paradox of keeping everything running and at the same time changing everything. To be able to achieve this, organizations must create the capacity for continuous change, learning and improvement. The permanence of change demands a permanence of adaptive and creative behaviour on the part of organizations and requires managers to continually upgrade the skills and performance of employees and their own. Such constant improvement increases both personal and organizational effectiveness. Developing the human resources (employee) in this way involves training and development activities. It is against this backdrop that this paper underscores the indispensability of training development on human resources effectiveness in organizations. This paper relies on secondary data collected from books and journal articles, and was content analyzed in relation to the scope of the paper. The paper concludes that the reasons organizations train and develop their workforce continually are to maintain effective performance, improve the quality of decision-making and raise the quality and timeliness of service delivery in today’s competition business environment.